Participative policymaking in complex welfare system : a Delphi study - Pernaa, Hanna-Kaisa (Springer, 2020)
Shared, experience driven and value based perspectives in an ongoing interaction of agents constitute the basis of the co-evolutionary dynamic of a complex system. The interpretation of good governance comprehends participation as increasingly fundamental in approaching policies in complex systems. This chapter presents a Delphi-study of the possibilities and obstacles of participative policymaking (PPM) in municipal welfare services viewed by an expert panel consisting of 37 participants representing the executive managers of 3rd sector organizations, the chairmen of the municipal councils or welfare service boards and the leading office-holders of municipal welfare offices in Finland. The panel estimated and discussed the projections of participatory welfare policy making in 2030. The outcomes of the study indicate that regardless of technological preparedness and the structural opportunities offered by a reform, cultural inertia and unawareness generate attitudes inhibitory on PPM practices. Albeit participative practices were considered influential to poli-cymaking legitimacy as well as central to the nature of equal and flexible resource distribution, there were reservations about the inclusion of the participation. There were concerns over the validity and the liability of the decisions reached by participative means. Several undercurrents affecting the development of PPM were discernible in the conversations.
Keywords: well-being; social services; welfare state; participation; public administration; public services; welfare policy; welfare services; basic public services; development (active); fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|